MapHead : the return - Howarth, Lesley (Cambridge, Mass. : Candlewick Press, 1997)
MapHead, a boy with strange powers from a parallel dimension, finds himself alone without his father for the first time and returns to Rubytown to find his own destiny.
Sequel to: MapHead.
Bulletin (Center for Children's books).
Horn Book.
School Library Journal.
Young Adult
Keywords: Fourth dimension -- Fiction; Friendship -- Fiction; MapHead (Fictitious character) -- Fiction; Science fiction; Fourth dimension -- Fiction; Friendship -- Fiction; MapHead (Fictional character) -- Fiction; Science fiction